Hepatitis B vaccine nonresponders: Possible mechanisms and solutions - Saco, Tara Vinyette; Strauss, Alexandra T; Ledford, Dennis K (Annals of allergy, asthma, & immunology, 2018)
Hepatitis B (HBV) is a viral illness that chronically infects 240 million people worldwide, leads to liver disease, and increases risk of hepatocellular carcinoma. The HBV vaccine has decreased HBV infection, and it and the human papilloma virus vaccine are the only vaccines that prevent cancer. Despite the effectiveness of the HBV vaccine, some populations do not develop protective responses. The risk groups for poor response include those with immunosuppression or dialysis-dependent, end-stage renal disease. Five percent of normal people do not have a response. These subjects are deemed HBV "nonresponders." Multiple strategies to improve the immunogenicity of the HBV vaccine are currently being pursued, including vaccine adjuvants, recombinant vaccines, and immune enhancement via up-regulation of dendritic cells. PubMed was searched for peer-reviewed publications published from January 1980 to September 2017. Studies retrieved for inclusion summarized potential mechanisms behind HBV vaccine nonresponsiveness and potential solutions. The mechanisms behind HBV vaccine nonresponsiveness vary between each subject population. Many current and future strategies may provide protective immunity against HBV in each of these populations. This review provides a background on the immunology of HBV infection, the possible immunologic mechanisms to explain HBV vaccine nonresponsiveness, current research aimed at improving vaccine effectiveness, and possible future approaches for providing nonresponders protection from HBV.